LL-01 Social determinants of treatment adherence and disease severity among people living with lupus in a small island developing state: a report from St. Lucia. (August 2018) - King, Amanda; Altenor, Cleopatra; Brown, Catherine; Hambleton, Ian
Abstract : Background: The occurrence of systemic lupus erythematosus (SLE) varies considerably worldwide, with documented high incidence rates among women of African descent. The clinical course is likely influenced by social determinants, including socioeconomic position (SEP), yet findings remain inconsistent, with little information from the Caribbean diaspora. This study presents the epidemiology of SLE in St. Lucia for the first time, exploring the association of SEP and SLE medication adherence and disease severity. Methods: Data have been collected from the only specialist lupus clinic in St Lucia between 1995 and 2017. We explored the effect of selected markers of SEP on disease severity (yes/no), and treatment adherence (yes/no) using logistic regression, adjusting for the effects of age, sex and years since diagnosis at all times. We used education level (primary or secondary education, tertiary education) or patients eligible for treatment cost discount or exemption (yes/no) as indicators of SEP. We also explored the effect of enrolment in a self-help programme on both regression outcomes, and the effect of treatment adherence on disease severity. Results: 143 people with SLE have registered at the clinic between 1995 and 2017. The mean age at diagnosis was 32 years (standard deviation 12 years), and 132 (92%) were female, for a female to male ratio of 12 to 1. Since 2010 (a period of full clinic operation) 66 women have been diagnosed with SLE, for a crude incidence rate of 9.3 per 1 00 000 person years (95% CI 7.2 to 11.8). Half (49%) had a severe clinical course, defined as having cerebritis, nephritis, or being on dialysis, and half (50%) were medication adherent at their last follow-up visit. Higher SEP was consistently associated with increased treatment adherence and decreased disease severity (treatment adherence odds ratios ranged from 2.4 to 3.4; disease severity odds ratios ranged from 1.0 to 3.5) (figure 1). Conclusion: In St Lucia, among a population of predominantly African descent, and using selected markers of SEP, patients of lower socioeconomic position have more severe disease and lower medication adherence than those of higher socioeconomic position. Acknowledgements: Christina Howitt, for assistance with data analysis.